2013
DOI: 10.1097/qai.0b013e31828a3e60
|View full text |Cite
|
Sign up to set email alerts
|

High HIV Prevalence Among Men Who Have Sex With Men in Nigeria

Abstract: HIV prevalence among MSM in the 3 cities was 4-10 times higher than the general population prevalence and was behaviorally linked. In response to a complex set of risks and disadvantages that put African MSM at a greater risk of HIV infection, future interventions targeting MSM should focus on a comprehensive approach that combines behavioral, biomedical, and structural interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 30 publications
9
57
0
Order By: Relevance
“…1 A more recent survey also using RDS and serological testing reported an HIV prevalence among MSM of 34.9% in Abuja, 11.3% in Ibadan and 15.2% in Lagos. 2 In comparison, the national HIV prevalence in Nigeria is estimated at 4.1%. 3 The pattern of a disproportionately high prevalence of HIV among MSM within a generalised epidemic setting is consistent across African countries, including those in sub-Saharan Africa with an exceedingly high national HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A more recent survey also using RDS and serological testing reported an HIV prevalence among MSM of 34.9% in Abuja, 11.3% in Ibadan and 15.2% in Lagos. 2 In comparison, the national HIV prevalence in Nigeria is estimated at 4.1%. 3 The pattern of a disproportionately high prevalence of HIV among MSM within a generalised epidemic setting is consistent across African countries, including those in sub-Saharan Africa with an exceedingly high national HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…The results and details of the HIV testing process have been presented in a separate publication. 2 The survey instrument was adapted from a previous study and tested before the field data collection. 13 Participants and recruitment MSM were defined as men aged ≥18 years living in the cities of Abuja, Ibadan and Lagos who reported oral or anal sex with another man in the past 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…This study population was chosen, because previous studies carried out among MSM in Nigeria showed that the majority of self-reported MSM were younger than 30 years of age. [30][31][32] It is hoped that the findings from this research will contribute to filling the gap in knowledge available on this topic. This article focuses particularly on our analysis of the differences between medical and nonmedical students.…”
mentioning
confidence: 99%
“…In Nigeria, for example, Vu, Adebajo et al [22] report HIV prevalence rates ranging from 11.3 to 34.9 % among MSM in three cities, and note that these rates are 4-10 times higher than HIV prevalence in the general population. In a cohort study in Senegal, Drame et al [23] report an HIV prevalence of 36 %, while in Togo Ekouevi, Dagnra et al [24] report a prevalence of 19.6 % in a cross sectional study in six cities.…”
Section: The Epidemiology Of Hiv In Msm In Ssamentioning
confidence: 95%
“…In terms of HIV infection, Park et al [25] found that gay self identity was associated with being HIV positive among MSM in Douala, Cameroon (OR2.53; 95 % confidence interval (CI) 1.90-7.40), and Vu, Adebajo et al [22] found that heterosexual and bisexual MSM in Ibadan, Nigeria, were significantly more likely to be HIV positive than gay identifying MSM in that city (AOR 9.1; 95 % CI 1.2-70.6).…”
Section: Drivers Of Risk In Msm Local Environmentsmentioning
confidence: 98%